Granulomatous lesions and Mycobacterium avium Subsp. paratuberculosis in Portuguese wild boars (Sus scrofa) - Matos, Ana Cristina (2013)
Wild boar (Sus scrofa) is considered a vector of mycobacterial infections, but the presence of Mycobacterium avium subsp. paratuberculosis (MAP) has never been assessed in this species in Portugal.